Terapi L-Ascorbic Acid 10% dan Glutation 2% Dibandingkan dengan Hidrokuinon 4% pada Pasien Melasm - Ummi Rinandari; Putti Fatiharani Dewi; Arie Kusumawardani; Muhammad Eko Irawanto; Moerbono Mochtar (Syntax Corporation Indonesia, 2021)
Melasma is a hyperpigmentation disorder that is often found, is chronic. Hydroquinone is considered the standard therapeutic standard of melasma, has limitations and side effects vary. L-ascorbic acid acts as a reactive oxygen species (ROS) scavenger and has the ability to bind copper ions in the tyrosinase workplace. Glutation has the function of depigmentation of the skin that inhibits melanogenesis by suppressing the activity of tyrosinease enzymes. The purpose of this study was to prove and analyze the effectiveness of serum combination therapy L-ascorbic acid 10% and glutation 2% in lowering MASI score compared to serum hydroquinone 4% in melasma patients. Clinical experimental research method, pre and posttest double blind randomized controlled trial with the study subjects as many as 36 melasma patients. In group I was given a combination of serum L-ascorbic acid 10% and glutation 2%, while group II got serum hydroquinone 4%. The effectiveness of serum is assessed with an MASI score. The analyses used are t-paired tests, Wilcoxon tests and Difference-in-Differences (DID) analyses. Statistical tests are considered meaningful if p<0.05. The results of the study in both groups had a significant decrease in MASI score (p<0,001), but the decrease did not differ significantly between the two groups. The decrease in MASI scores between the two groups made no significant difference in week 4 (p=0.535) and 8th (p=0.303). The conclusion of this study was a combination of serum L-ascorbic acid 10% and glutation 2% lowered MASI score, but not proven more effective in lowering MASI score than serum hydroquinone 4% in melasma patients.